Pentaploidization Enriches the Genetic Diversity of Wheat by Enhancing the Recombination of AB Genomes - Yang, Fan; Wan, Hongshen; Li, Jun; Wang, Qin; Yang, Ning; Zhu, Xinguo; Liu, Zehou; Yang, Yumin; Ma, Wujun; Fan, Xing; Yang, Wuyun; Zhou, Yonghong (Frontiers in Plant Science, 2022)
Allohexaploidization and continuous introgression play a key role in the origin and evolution of bread wheat. The genetic bottleneck of bread wheat resulting from limited germplasms involved in the origin and modern breeding may be compensated by gene flow from tetraploid wheat through introgressive hybridization. The inter-ploidy hybridization between hexaploid and tetraploid wheat generates pentaploid hybrids first, which absorbed genetic variations both from hexaploid and tetraploid wheat and have great potential for re-evolution and improvement in bread wheat. Therefore, understanding the effects of the pentaploid hybrid is of apparent significance in our understanding of the historic introgression and in informing breeding. In the current study, two sets of F2 populations of synthetic pentaploid wheat (SPW1 and SPW2) and synthetic hexaploid wheat (SHW1 and SHW2) were created to analyze differences in recombination frequency (RF) of AB genomes and distorted segregation of polymorphic SNP markers through SNP genotyping. Results suggested that (1) the recombination of AB genomes in the SPW populations was about 3- to 4-fold higher than that in the SHW populations, resulting from the significantly (P < 0.01) increased RF between adjacent and linked SNP loci, especially the variations that occurred in a pericentromeric region which would further enrich genetic diversity; (2) the crosses of hexaploid × tetraploid wheat could be an efficient way to produce pentaploid derivatives than the crosses of tetraploid × hexaploid wheat according to the higher germination rate found in the former crosses; (3) the high proportion of distorted segregation loci that skewed in favor of the female parent genotype/allele in the SPW populations might associated with the fitness and survival of the offspring. Based on the presented data, we propose that pentaploid hybrids should increasingly be used in wheat breeding. In addition, the contribution of gene flow from tetraploid wheat to bread wheat mediated by pentaploid introgressive hybridization also was discussed in the re-evolution of bread wheat.